Corona virus and human rights - Kjaerum, Morten; Davis, Martha F., 1957-; Lyons, Amanda ([Great Barrington, Massachusetts] American Institute for Economic Research (AIER), 2020)
"This collection explores the COVID-19 pandemic and its global effects on human rights. The contributors argue that a human rights perspective is necessary to understand the pervasive consequences of the crisis, while focusing attention on those being left behind and providing a necessary framework for the effort to 'build back better.' Expert contributors to this volume address interconnections between the COVID-19 crisis and human rights to equality and non-discrimination, including historical responses to pandemics, populism and authoritarianism, and the rights to health, information, water access, and the environment. Highlighting the dangerous potential for derogations from human rights, authors further scrutinise the human rights compliance of new legislation and policies in relation to issues such as privacy, protection of persons with disabilities, freedom of expression and access to medicines"--
'Human rights against human arbitrariness' : pandemics in a human rights historical perspective / Steven L. B. Jensen -- Human-rights-based versus populist responses to the pandemic / t COVID-19 risk communication : the right to information and participation / Tove H. Malloy -- The human (rights) costs of inequality : snapshots from a pandemic / Martha F. Davis -- Racial justice to the forefront : do Black lives matter in international law? / t COVID-19 and the human rights to water and sanitation / Pedi Obani -- Land rights in crisis / Juliana Nnoko-Mewanu -- How the pandemic has impacted the various layers of the global garment supply chain / Sanchita Banejee Saxena, Harpreet Kaur and Salil Tripathi -- Campaigning for both innovation and equitable access to COVID-19 medicines / Brook Baker -- Is COVID-19 frustrating or facilitating sustainability transformations? : an assessment from a human rights law perspective / Claudia Ituarte-Lima -- The post-crisis human rights agenda / Morten Kjaerum
Includes bibliographical references and index.
Keywords: Corona (Disease) -- Political aspects; COVID-19 (Disease) -- Social aspects; Human rights; Human rights; Human security